Break the wall : why and how to democratize digital in your business - Aksehirli, Zeynep; Bart, Yakov; Chan, Kwong; Pauwels, Koen (American Marketing Association, 2022)
Break the Wall: Why and How to Democratize Digital in your Business examines problems facing business units and top management adapting to digital transformation and offers solutions. Each department within a business has important, but distinct responsibilities, and very different speeds of digital transformation. Parts of an organisation that touch the outside world will often be first to sense a need. Their adaptive changes can then cascade up, and as this is implemented more widely the organization builds value and resilience. The structure of this book is built upon real-world issues the authors encountered in their research and consultancy, with each chapter offering a specific solution. The new framework presented here was inspired by dozens of interviews with digital transformation experts and by an ecological model that aims to understand resilience in the biological world by looking at continuous and nesting adaptation cycles of ecosystems. This book forms part of the American Marketing Association (AMA) series.